Simulation of Paper Processing in High Frequency Electromagnetic Field with the Help of a Specific Software - RUS Daiana Ioana; SZOKE Adrian; MUȚIU Tudor George; SOPRONI Vasile Darie; MOLNAR Carmen Otilia (Journal of Electrical and Electronics Engineering)
A very important category of applications of the high-frequency electromagnetic field concerns the direct action of the microwave field on materials capable of absorbing some of the received energy and converting it into heat. The use of microwave energy (MW) can be considered as a controlled heating source, which can also be used in combination with other heating methods. The great advantage of this type of heating is that the power is distributed throughout the load mass. Based on these considerations, the present work aims to analyze the electric field distribution on the surface of a dielectric whose dielectric loss and loss angle tangent correspond to those of office paper, simulated for different humidity values. The results on the electromagnetic field distribution in the dielectric are emphasized by the complex electric field component which were obtained with a specific software. It is known that the existence of such software reduces the workload but if we pursue the optimization of the installations, it increases the number of simulations required.